A review of shale gas prospects from nonmarine shales in Indonesia and Malaysia - A new beginner in shale gas play - Nugraheni, R.D. (European Association of Geoscientists and Engineers, EAGE, 2013)
The key challenges for future energy resources of the worlds are expected from unconventional resources. Indonesia and Malaysia are neighboring countries which endeavor to discover shale gas. Therefore, a review of the non-marine Tertiary shales in the Pematang Group and Bampo Formation of the Central and North Sumatra Basin, Indonesia as well as the Balingian Formation of the Balingian sub-Basin, Malaysia would give an insight into their potential. Samples of the Pematang Group are taken from well drilling, while Bampo and Balingian Formations are taken from rock exposures. In Pematang Group, zone of interest is depicted from Brown Shale member with lacustrine facies. Thick sequences of immature to mature were noted as very good to excellent TOC content, potential source for gas (as denoted by >6 of potential yield) and high Tmax. The same facies of Bampo Formation shows fair TOC value, in the range of 0.76 to 0.84. Combination of typical II and III were observed in both. The Balingian Formation displays deltaic-estuarine facies. The presence of coal bearing may support the interpretation of type III kerogen with rich in organic matter. Quartz-rich horizon is one of essential factor to determine interest zone for fracture stimulation. Copyright Â© (2012) by the European Association of Geoscientists & Engineers All rights reserved.